DESIGN AND IMPLEMENTATION OF A MOBILE OPEN DONATION PLATFORM WITH PAYMENT GATEWAY INTEGRATION - M. Irpan; Nur Maysabila; Nanang Agustiar; Firman Putra Pratama; Nejad Ahmed Al-Hadad; David Suprianto Sianturi (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The rapid development of information technology has encouraged the transformation of conventional donation systems into digital-based platforms that are more accessible, transparent, and efficient. This study aims to design and develop a mobile-based open donation application to facilitate digital donation activities for students and the general public. The system was developed using the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and evaluation stages. Data collection was conducted through observations and interviews to identify user needs and problems in manual donation management processes. The application was developed using the Flutter framework with Firebase Authentication and Firebase Firestore as the backend system. The main features implemented include user registration and login, donation campaign lists, donation amount input, payment gateway integration, donation history, and admin management features. System testing was conducted using the Black Box Testing method to evaluate application functionality. The testing results showed that all application features operated properly without significant functional errors. The integration of Firebase successfully supported real-time data storage and user authentication processes, while the payment gateway integration enabled online donation transactions to be performed more easily and securely. In addition, the donation history feature increased transparency and user trust in donation management. The developed application is expected to improve the effectiveness, transparency, and accessibility of digital donation management while encouraging greater public participation in social and humanitarian activities.